Virtual Care: Counseling Experiences of Guidance Counselors and Clients in the New Normal - Ignacio, Darwin Fernandez (International Journal of Applied Guidance and Counseling, 2023)
This qualitative phenomenological study explored the online counseling experiences of guidance counselors and clients in the new normal. Using purposeful sampling, ten participants, precisely five guidance counselors and five clients, actively participated in the semi-structured interviews. Results revealed eleven themes to answer the central question of the study. Three emergent themes described the challenges faced by guidance counselors in online counseling. They were (1) means of delivery, (2) counseling engagement, and (3) conduciveness of counseling sessions. In addition, three emergent themes described their insights upon facing the challenges. They were (1) online impediments, (2) online convenience, and (3) avenue for self-guided improvement. On the other hand, three emergent themes described clients' reasons for seeking online counseling. They were (1) psychological and academic related concerns, (2) express emotions and private issues, and (3) personal and referral drives. Lastly, two emergent themes described their views towards online counseling. They were (1) presence of virtual care and (2) acknowledgment of online counseling existence.Â